Development of Balancing Act Recovery Model for Falling Prevention - silarak, Kanyapak; Leethong, Paphawin; Ruangsawat, Piyanoot; Palaree, Panatda (Medical Journal of Sakon Nakhon Hospital, 2024)
The objective of this study was to develop the balancing act recovery model for falling prevention by applying the Mini–BESTest assessment and compare the balancing act ability before and after applying the balancing act recovery model. The samples were 80 elderly persons. The study was conducted from June 7th to October 15, th 2022 at Phra Ajarn Fan Arjaro hospital. The study tools were the balancing act recovery model for falling prevention, questionnaire and physical fitness test. The content validity was examined by 3 experts and content validity index was 0.97. The tool reliability was 0.82. Data were analyzed by using the descriptive statistics, Chi–square test, paired t–test statistics and Independent t–test. The results of the study showed that before using the balancing act recovery model for falling prevention, there was no statistically significant difference (p > 0.05) in the level of balance act ability between the experimental and control group. However, after using the balancing act recovery model for falling prevention, their levels of balancing act ability were significantly different (p < 0.01). The level of balance act ability in experimental group after using the model was improved significantly (p < 0.01). The findings indicated that the development of the balancing act recovery model for falling prevention was able to improve the the geriatric balance rehabilitation.